Islamic perspective on end of life issues in persistent vegetative state patients - a case report - Rathor, Mohammad Yousuf; Draman, Che Rosle (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Persistent vegetative state (PVS) is a clinical condition of unawareness of self and environment with preserved sleep-wake cycles. Its clinical diagnosis can be a difficult unless a physician has adequate experience and expertise in evaluating neurological syndromes. Outcome is based on aetiology and age. Decisions on limiting life-sustaining treatment (LST) for these patients are emotionally and morally challenging. We present a case of a young boy who went into PVS following traumatic brain injury (TBI) with the aim to review some of the ethical issues regarding its management from Islamic perspective.